Memantine effects measured with the Relevant Outcome Scale for Alzheimer's disease in an open‐label, single‐arm, multicenter clinical study. (11th April 2012) - Holthoff, Vjera; Ferris, Steven; Gauthier, Serge; Ihl, Ralf; Robert, Philippe; Winblad, Bengt; Sternberg, Kati; Tennigkeit, Frank; ,
<x xml:space="preserve">Abstract</x> Objective The Relevant Outcome Scale for Alzheimer's disease (ROSA) is a novel, valid, and reliable instrument for multidimensional assessment of Alzheimer's disease (AD) symptoms across all severity stages. The ROSA and four standard instruments — the Alzheimer's disease Assessment Scale‐cognitive (ADAS‐cog), Severe Impairment Battery (SIB), Disability Assessment for Dementia (DAD), and the Neuropsychiatric Inventory (NPI) — were used in an open‐label, multicenter, single‐arm clinical study to assess treatment‐induced changes in cognitive, functional, and behavioral symptoms in patients with AD at different severity stages. Methods A total of 451 patients were treated with memantine (initiated at 5 mg/day and up‐titrated with 5 mg weekly to a final dose of 20 mg/day) for 12 weeks. The study endpoints comprised changes from baseline in the scores of the ROSA, ADAS‐cog, SIB, DAD, and NPI as well as global changes on the Clinical Global Impression of Change (CGI‐C). Analyses were performed for the overall population and by AD severity stage (early, middle, late). Results The ROSA scores increased significantly after a 12‐week treatment in all study groups except for early stage. Mean changes in the ADAS‐cog score indicated a trend towards worsening in early and middle stages. Non‐significant changes were shown by the SIB, NPI, and DAD assessments at week 12. The CGI‐C demonstrated 'minimal improvement' or 'no change' for most of the patients. Overall, memantine treatment was safe and well tolerated. Conclusion The results demonstrated the ROSA feasibility in daily practice for assessment of memantine effects over time in patients with moderate and late AD. Copyright © 2012 John Wiley & Sons, Ltd.